Adsorption of Cu 2+ Adsorbent and preparation method thereof
By preparing a gel sponge carrier with amine groups, pre-adsorbing Cu2+ in the alkali solution, and then desorbing it in the acid solution, an adsorbent that efficiently adsorbs Cu2+ is obtained, and the raffinate in the copper hydrometallurgy process is solved. The problem of high Fe content in the treatment achieves efficient purification and concentration of copper.
Patent Information
- Application Number
- CN202210758324.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-06-29
AI Technical Summary
In the existing copper hydrometallurgy process, the raffinate after the extraction process still contains copper with high Fe content, which is difficult to process, and reusing it to the extraction section will increase the processing volume and reduce the Cu2+ concentration.
By adopting a method of preparing an adsorbent for adsorbing Cu2+, a gel sponge carrier with an amine group is prepared, and after crosslinking, it is shaken in the alkali solution to pre-adsorb Cu2+, and then desorption in the acid solution, obtaining high Adsorption selectivity and high adsorption capacity adsorbents.
It realizes efficient adsorption of copper ions, improves the purification and concentration effect of copper, and solves the problem of processing high Fe content in raffinate.
Smart Images

Figure CN117358210B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of adsorption technology, and more specifically, to the adsorption of Cu 2+ Adsorbent and preparation method thereof. Background Art
[0002] More than 80% of the world's copper is extracted from copper sulfide ores through pyrometallurgical smelting, and the beneficiation process of copper sulfide ores is relatively simple, so pyrometallurgy has become the main method of producing copper in the world today, but this method is only suitable for high-grade copper ores. Modern hydrometallurgical copper smelting technology mainly recovers copper from low-grade ores that are difficult to use by pyrometallurgy, such as oxide ores, difficult-to-select sulfide ores, stripped off-surface ores, flotation tailings, and abandoned mines. The modern copper hydrometallurgical process is mainly divided into three parts: leaching-extraction-electrodeposition. The extraction part is a key step that connects the past and the future. It has good impurity removal and concentration effects and is widely used. However, the raffinate after the extraction process still contains a certain amount of copper, which has a certain value, but its Fe content is high and difficult to handle. If it is reused in the extraction section, it will not only greatly increase the processing capacity of the extraction section, but also reduce the Cu in the initial solution before extraction. 2+ Therefore, there are still technical difficulties in copper smelting. Summary of the invention
[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a method for preparing Cu adsorbed 2+ The adsorbent prepared by the method has a better adsorption effect on copper ions.
[0004] In one aspect of the present invention, the present invention provides a method for preparing a Cu adsorbent. 2+ According to an embodiment of the present invention, a method for preparing an adsorbent for Cu 2+ The method for preparing an adsorbent comprises: preparing a gel sponge carrier, wherein the gel sponge carrier has an amino group; placing the gel sponge carrier in a first mixed solution for a predetermined reaction time to obtain a cross-linked sponge carrier, wherein the first mixed solution comprises a cross-linking agent and Cu 2+ ; The cross-linked sponge carrier is placed in an alkaline solution containing carbon disulfide and shaken for a predetermined time to obtain a pre-adsorbent; The pre-adsorbent is placed in an acid solution to react for a certain time, and then washed and dried to obtain the adsorbent. Therefore, the adsorbent prepared by the above preparation method has a high adsorption selectivity and high adsorption capacity for copper ions.
[0005] According to an embodiment of the present invention, the method for preparing the gel sponge carrier includes: providing a polyethyleneimine solution and an alginate solution, wherein the pH value of the polyethyleneimine solution is 6.2 to 6.8; adding the polyethyleneimine solution to the alginate solution to obtain a second mixed solution; and freezing the second mixed solution to obtain the gel sponge carrier.
[0006] According to an embodiment of the present invention, the polyethyleneimine in the polyethyleneimine solution is branched polyethyleneimine, including primary amine groups, secondary amine groups and tertiary amine groups.
[0007] According to an embodiment of the present invention, the mass percentage of polyethyleneimine in the polyethyleneimine solution is 2% to 8%, and the concentration of alginate in the alginate solution is 0.5% to 1.2%.
[0008] According to an embodiment of the present invention, the temperature of the freezing treatment is 0°C to -80°C.
[0009] According to an embodiment of the present invention, the cross-linking agent includes genipin, and the mass percentage of the genipin in the first mixed solution is 0.3% to 0.7%, and / or the cross-linking agent includes glutaraldehyde, and the mass percentage of the glutaraldehyde in the first mixed solution is 0.25% to 0.60%.
[0010] According to an embodiment of the present invention, in the first mixed solution, Cu 2+ The concentration is greater than 0 and less than or equal to 2g / L.
[0011] According to an embodiment of the present invention, the concentration of carbon disulfide in the alkali solution is 0.20 g / 250 mL to 1.20 g / 250 mL.
[0012] According to an embodiment of the present invention, the concentration of hydrogen ions in the acid solution is greater than or equal to 1 mol / L.
[0013] In another aspect of the present invention, the present invention provides a Cu adsorption 2+ According to an embodiment of the present invention, the adsorbent is prepared by the method described above. As a result, the adsorbent has high adsorption selectivity and high adsorption capacity for copper ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0015] Figure 1 It is a schematic diagram of the process of preparing an adsorbent in one embodiment of the present invention. DETAILED DESCRIPTION
[0016] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0017] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0018] In one aspect of the present invention, the present invention provides a method for preparing a Cu adsorbent. 2+ According to an embodiment of the present invention, referring to Figure 1 , preparation of adsorbed Cu 2+ The adsorbent methods include:
[0019] S100: preparing a gel sponge carrier, wherein the gel sponge carrier has an amino group. Thus, by using the sponge as a carrier, the finally prepared adsorbent is in a sponge shape, and compared with the granular adsorbent, solid-liquid separation after adsorption is easy, and the morphology is controllable, the acid and alkali resistance is good, and the applicability is strong.
[0020] According to an embodiment of the present invention, a method for preparing a gel sponge carrier comprises:
[0021] S110: Provide a polyethyleneimine solution and an alginate solution, wherein the pH value of the polyethyleneimine solution is 6.2 to 6.8 (e.g., pH 6.2, 6.3, 6.4, 6.5, 6.6, 6.7 or 6.8). Use alginate (e.g., sodium alginate) to make a sponge. Alginate (e.g., sodium alginate) is an extract of seaweed, which is readily available in large quantities and easily degradable, and will not cause adverse effects on the environment. Moreover, the pH value of the polyethyleneimine solution is 6.2 to 6.8, which will make the prepared gel sponge carrier have relatively excellent structural stability and good adsorption efficiency. If the pH value is lower than 6.2, the gel solidifies relatively quickly during the subsequent freezing process, resulting in a low porosity of the sponge, and then resulting in a low adsorption amount of copper ions. If the pH value is higher than 6.8, it will make it difficult to gelate later, and the stability of the prepared sponge will be poor.
[0022] S120: adding the polyethyleneimine solution to the alginate solution to obtain a second mixed solution;
[0023] In some embodiments, the polyethyleneimine in the polyethyleneimine solution is a branched polyethyleneimine, including primary amine groups, secondary amine groups and tertiary amine groups. Alginate has carboxyl groups, which can be cross-linked with protonated polyethyleneimine to obtain a stable gel sponge carrier. Moreover, the branched polyethyleneimine has three amine groups, namely, primary amine groups, secondary amine groups and tertiary amine groups, which can fully react with alginate to improve the structural stability of the gel sponge carrier.
[0024] According to an embodiment of the present invention, the mass percentage of polyethyleneimine in the polyethyleneimine solution is 2% to 8% (e.g., 2%, 3%, 4%, 5%, 6%, 7%, 8%), and the concentration of alginate in the alginate solution is 0.5% to 1.2% (e.g., 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%). As a result, the amine groups in polyethyleneimine react more fully with the carboxyl groups in alginate, thereby increasing the reaction rate of the raw materials.
[0025] S130: Freezing the second mixed solution to obtain a gel sponge carrier. Through freezing, a gel sponge carrier with a suitable porosity can be obtained.
[0026] According to an embodiment of the present invention, the temperature of the freezing treatment is 0°C to -80°C (for example, 0°C, -10°C, -20°C, -30°C, -40°C, -50°C, -60°C, -70°C, -80°C). Within the above temperature range, a gelled sponge carrier can be better obtained, and the sponge carrier has a suitable porosity, which helps to improve the adsorption efficiency of the adsorbent. If the temperature of the freezing treatment is too high, it is difficult to achieve a better freezing pore-forming effect, resulting in low sponge porosity and poor adsorption effect; if the temperature is too low, it cannot bring better adsorption effect, but instead causes energy waste.
[0027] S200: placing the gel sponge carrier in a first mixed solution and reacting for a predetermined time to obtain a cross-linked sponge carrier, wherein the first mixed solution comprises a cross-linking agent and Cu 2+ In this step, the amine groups in polyethyleneimine that have not reacted with the carboxyl groups in alginate are cross-linked with a cross-linking agent, thereby further enhancing the stability of the adsorbent, so that the adsorbent can treat highly acidic wastewater.
[0028] According to an embodiment of the present invention, the cross-linking agent includes genipin, and the mass percentage of the genipin in the first mixed solution is 0.3% to 0.7% (such as 0.3%, 0.4%, 0.5%, 0.6%, 0.7%), and / or, the cross-linking agent includes glutaraldehyde, and the mass percentage of the glutaraldehyde in the first mixed solution is 0.25% to 0.60%. The above-mentioned cross-linking agent and the concentration of the cross-linking agent can be fully cross-linked with the gel sponge carrier, which can better improve the stability of the adsorbent and improve the adsorption efficiency of the adsorbent. If the concentration of the cross-linking agent is on the low side, the stability of the sponge-like adsorbent will be relatively poor. If the concentration of the cross-linking agent is on the high side, the adsorption effect on copper ions will be relatively reduced.
[0029] According to an embodiment of the present invention, in the first mixed solution, Cu 2+ The concentration is greater than 0 and less than or equal to 2 g / L (for example, 0.5 g / L, 1 g / L, 1.5 g / L, 1.8 g / L, 2 g / L). Thus, the addition of copper ions can occupy a position on the adsorbent in advance, and when the adsorbent prepared subsequently is adsorbed, the adsorption selectivity of copper ions is higher, which is more conducive to improving the adsorption efficiency of the adsorbent. If the concentration of copper ions is too high, the adsorption efficiency of the adsorbent cannot be further improved, but it will cause a waste of raw materials.
[0030] S300: placing the cross-linked sponge carrier in an alkaline solution containing carbon disulfide (CS2) and shaking it for a predetermined time to obtain a pre-adsorbent. In this step, the coordination atom S in carbon disulfide is in situ fixed in the pre-adsorbent through an affinity addition reaction, thereby further improving the adsorption effect.
[0031] According to an embodiment of the present invention, the concentration of carbon disulfide in the alkali solution is 0.20g / 250mL to 1.20g / 250mL (for example, 0.20g / 250mL, 0.3g / 250mL, 0.4g / 250mL, 0.5g / 250mL, 0.6g / 250mL, 0.7g / 250mL, 0.8g / 250mL, 0.9g / 250mL, 1.00g / 250mL, 1.20g / 250mL). Within the above concentration range, the obtained sponge-like adsorbent has a better adsorption effect on copper ions and has better stability. If the concentration of carbon disulfide is low, the adsorption effect is relatively biased; if the concentration of carbon disulfide is high, too much secondary amine participates in the affinity addition reaction, resulting in the cross-linking disintegration of part of the alginate and polyethyleneimine, and the adsorbent stability is reduced.
[0032] There are no special requirements for the specific solution of the alkali solution, and those skilled in the art can flexibly select it according to actual conditions. For example, the alkali solution can be a sodium hydroxide solution, a potassium hydroxide solution, an ammonia solution, or the like.
[0033] S400: placing the pre-adsorbent in an acid solution for a certain period of time, washing with water, and drying to obtain an adsorbent. Thus, the hydrogen ions in the acid solution displace the copper ions attached in step S200 to obtain a copper ion imprinted sponge-like adsorbent, and then during the adsorption process of the adsorbent, the selectivity for copper ions is higher and the adsorption capacity is also higher.
[0034] According to an embodiment of the present invention, the concentration of hydrogen ions in the acid solution is greater than or equal to 1 mol / L. Thus, it can be effectively ensured that the copper ions are completely desorbed. There are no special requirements for the specific solution of the acid solution, and those skilled in the art can flexibly select it according to actual conditions. For example, the acid solution can be a solution of hydrochloric acid, nitric acid, sulfuric acid, etc., preferably hydrochloric acid and nitric acid.
[0035] According to an embodiment of the present invention, the adsorbent prepared by the above method has high selectivity and adsorption efficiency for copper ions. In some embodiments, it can be used for the purification and concentration of copper in Fe / Cu system solutions. Specifically, it can be applied to the raffinate after extraction of copper concentrate leachate to adsorb copper ions in the raffinate, thereby achieving the purification and concentration of copper. In practical applications, the copper hydrometallurgical process is mainly divided into three parts: leaching-extraction-electrodeposition, among which the extraction part is a key step that connects the past and the future. It has good impurity removal and concentration effects and is widely used. However, the raffinate after the extraction process still contains a certain amount of copper, which has certain value, but its Fe content is high and difficult to handle. If it is reused in the extraction section, it will not only greatly increase the processing capacity of the extraction section, but also reduce the Cu in the initial solution before extraction. 2+ At this time, the adsorbent of the present invention can be used to adsorb the copper ions in the raffinate after the copper concentrate leaching solution is extracted, thereby achieving the purification and concentration of copper.
[0036] In another aspect of the present invention, the present invention provides a Cu adsorption 2+ According to an embodiment of the present invention, the adsorbent is prepared by the method described above. As a result, the adsorbent has a high adsorption selectivity and high adsorption capacity for copper ions. It can be understood by those skilled in the art that the adsorbent Cu 2+ The adsorbent has all the characteristics and advantages of the method described above, which will not be described in detail here.
[0037] Example
[0038] In the following examples and comparative examples, the composition of the adsorption stock solution is shown in Table 1.
[0039] Table 1: Composition of adsorption stock solution
[0040]
[0041]
[0042] Adsorption amount calculation formula: q = (C eq -C0)*V*1000 / m1, where q (mg / g) is the adsorption capacity of the adsorbent; C0 and C eq (g / L) are the metal concentrations before and after the adsorption reaction; V(L) is the volume of the solution; m1(g) is the mass of the adsorbent.
[0043] The formula for the mass loss of the adsorbent after adsorption and desorption is: (m1-m2)*100 / m1, where m1 and m2 are the dry weight (g) of the adsorbent before adsorption and after desorption, respectively.
[0044] The porosity of the adsorbent is calculated by measuring its apparent density and true density. The calculation method is: porosity = (1-ρA / ρT) × 100%, where ρA is the apparent density of the sponge, in kg / m 3 ; ρT is the true density of the sponge, in kg / m 3 .
[0045] Separation factor (α Cu / M , where M represents Fe 3+ or Zn 2+ ) is calculated by the following formula:
[0046] α Cu / M =q Cu *C eq,M / (q M *C eq,Cu ), where q M (mg / g) is the adsorption amount of Fe or Zn by the adsorbent, C eq,Cu (g / L) is the concentration of Cu ions after adsorption, q Cu (mg / g) is the adsorption amount of Cu by the adsorbent, C eq,M (g / L) is the concentration of Fe or Zn ions after adsorption. Cu / M The larger the value, the better the selectivity of the adsorbent for Cu relative to M metal.
[0047] Example 1
[0048] Step 1: prepare 35 mL of a 4% branched polyethyleneimine solution, adjust the pH to 6.5 with nitric acid, slowly add the solution into 500 mL of a 0.8% sodium alginate solution while stirring to obtain a second mixed solution, pour the second mixture into a container and place it in a -50°C environment for rapid freezing for 5 hours to obtain a gel sponge carrier;
[0049] Step 2: Place the gel sponge carrier in 250 mL of the first mixed solution, which contains 0.5% genipin (w / w) and 1 g / L Cu 2+, and then slowly shaken at room temperature for 5 hours to obtain a cross-linked sponge carrier;
[0050] Step 3: Place the cross-linked sponge carrier in 250 mL of alkaline solution containing 0.625 g of carbon disulfide and shake slowly for 5 hours;
[0051] Step 4: Place the sponge obtained in step 3 in 250 mL of 1 M hydrochloric acid solution, desorb the copper ions, wash with water, and air-dry to obtain an adsorbent, and use the adsorbent to conduct an adsorption experiment. The adsorbent is numbered APS-1.
[0052] Example 2
[0053] Step 1: prepare 35 mL of a 4% branched polyethyleneimine solution, adjust the pH to 6.2 with nitric acid, slowly add the solution into 500 mL of a 0.8% sodium alginate solution while stirring to obtain a second mixed solution, pour the second mixture into a container and place it in a -50°C environment for rapid freezing for 5 hours to obtain a gel sponge carrier;
[0054] Step 2: Place the gel sponge carrier in 250 mL of the first mixed solution, which contains 0.5% genipin (w / w) and 1 g / L Cu 2+ , and then slowly shaken at room temperature for 5 hours to obtain a cross-linked sponge carrier;
[0055] Step 3: Place the cross-linked sponge carrier in 250 mL of alkaline solution containing 0.625 g of carbon disulfide and shake slowly for 5 hours;
[0056] Step 4: Place the above sponge in 250 mL of 1 M hydrochloric acid solution, desorb the copper ions, wash with water, and air-dry to obtain an adsorbent, and use the adsorbent to conduct an adsorption experiment. The adsorbent is numbered APS-2.
[0057] Example 3
[0058] Step 1: prepare 35 mL of a 4% branched polyethyleneimine solution, adjust the pH to 6.8 with nitric acid, slowly add the solution into 500 mL of a 0.8% sodium alginate solution while stirring to obtain a second mixed solution, pour the second mixture into a container and place it in a -50°C environment for rapid freezing for 5 hours to obtain a gel sponge carrier;
[0059] Step 2: Place the gel sponge carrier in 250 mL of the first mixed solution, which contains 0.5% genipin (w / w) and 1 g / L Cu 2+ , and then slowly shaken at room temperature for 5 hours to obtain a cross-linked sponge carrier;
[0060] Step 3: Place the cross-linked sponge carrier in 250 mL of alkaline solution containing 0.625 g of carbon disulfide and shake slowly for 5 hours;
[0061] Step 4: Place the above sponge in 250 mL of 1 M hydrochloric acid solution, desorb the copper ions, wash with water, and air-dry to obtain an adsorbent, and use the adsorbent to conduct an adsorption experiment. The adsorbent is numbered APS-3.
[0062] Example 4
[0063] Step 1: prepare 35 mL of a 4% branched polyethyleneimine solution, adjust the pH to 6.5 with nitric acid, slowly add the solution into 500 mL of a 0.8% sodium alginate solution while stirring to obtain a second mixed solution, pour the second mixture into a container and place it in a -10°C environment for rapid freezing for 5 hours to obtain a gel sponge carrier;
[0064] Step 2: Place the gel sponge carrier in 250 mL of the first mixed solution, which contains 0.5% genipin (w / w) and 1 g / L Cu 2+ , and then slowly shaken at room temperature for 5 hours to obtain a cross-linked sponge carrier;
[0065] Step 3: Place the cross-linked sponge carrier in 250 mL of alkaline solution containing 0.625 g of carbon disulfide and shake slowly for 5 hours;
[0066] Step 4: Place the above sponge in 250 mL of 1 M hydrochloric acid solution, desorb the copper ions, wash with water, and air-dry to obtain an adsorbent, and use the adsorbent to conduct an adsorption experiment. The adsorbent is numbered APS-4.
[0067] Comparative Example 1
[0068] Step 1: prepare 35 mL of a 4% branched polyethyleneimine solution, adjust the pH to 6.5 with nitric acid, slowly add the solution into 500 mL of a 0.8% sodium alginate solution while stirring to obtain a second mixed solution, pour the second mixture into a container and place it in a -50°C environment for rapid freezing for 5 hours to obtain a gel sponge carrier;
[0069] Step 2: Place the gel sponge carrier in 250 mL of the first mixed solution, which contains 0.5% genipin (w / w) and 0 g / L Cu 2+ , and then slowly shaken at room temperature for 5 hours to obtain a cross-linked sponge carrier;
[0070] Step 3: Place the cross-linked sponge carrier in 250 mL of alkaline solution containing 0.625 g of carbon disulfide and shake slowly for 5 hours;
[0071] Step 4: Place the above sponge in 250 mL of 1 M hydrochloric acid solution, desorb the copper ions, wash with water, and air-dry to obtain an adsorbent, and use the adsorbent to conduct an adsorption experiment. The adsorbent is numbered APS-0.
[0072] Example 5
[0073] Step 1: prepare 35 mL of a 4% branched polyethyleneimine solution, adjust the pH to 6.5 with nitric acid, slowly add the solution into 500 mL of a 0.8% sodium alginate solution while stirring to obtain a second mixed solution, pour the second mixture into a container and place it in a -10°C environment for rapid freezing for 5 hours to obtain a gel sponge carrier;
[0074] Step 2: Place the gel sponge carrier in 250 mL of the first mixed solution, which contains 0.5% genipin (w / w) and 2 g / L Cu 2+ , and then slowly shaken at room temperature for 5 hours to obtain a cross-linked sponge carrier;
[0075] Step 3: Place the cross-linked sponge carrier in 250 mL of alkaline solution containing 0.625 g of carbon disulfide and shake slowly for 5 hours;
[0076] Step 4: Place the above sponge in 250 mL of 1 M hydrochloric acid solution, desorb the copper ions, wash with water, and air-dry to obtain an adsorbent, and use the adsorbent to conduct an adsorption experiment. The adsorbent is numbered APS-5.
[0077] Example 6
[0078] Step 1: prepare 35 mL of a 4% branched polyethyleneimine solution, adjust the pH to 6.5 with nitric acid, slowly add the solution into 500 mL of a 0.8% sodium alginate solution while stirring to obtain a second mixed solution, pour the second mixture into a container and place it in a -10°C environment for rapid freezing for 5 hours to obtain a gel sponge carrier;
[0079] Step 2: Place the gel sponge carrier in 250 mL of the first mixed solution, which contains 0.5% genipin (w / w) and 1 g / L Cu 2+ , and then slowly shaken at room temperature for 5 hours to obtain a cross-linked sponge carrier;
[0080] Step 3: Place the cross-linked sponge carrier in 250 mL of alkaline solution containing 0.20 g of carbon disulfide and shake slowly for 5 hours;
[0081] Step 4: Place the above sponge in 250 mL of 1 M hydrochloric acid solution, desorb the copper ions, wash with water, and air-dry to obtain an adsorbent, and use the adsorbent to conduct an adsorption experiment. The adsorbent is numbered APS-6.
[0082] Example 7
[0083] Step 1: prepare 35 mL of a 4% branched polyethyleneimine solution, adjust the pH to 6.5 with nitric acid, slowly add the solution into 500 mL of a 0.8% sodium alginate solution while stirring to obtain a second mixed solution, pour the second mixture into a container and place it in a -10°C environment for rapid freezing for 5 hours to obtain a gel sponge carrier;
[0084] Step 2: Place the gel sponge carrier in 250 mL of the first mixed solution, which contains 0.5% genipin (w / w) and 1 g / L Cu 2+ , and then slowly shaken at room temperature for 5 hours to obtain a cross-linked sponge carrier;
[0085] Step 3: Place the cross-linked sponge carrier in 250 mL of alkaline solution containing 1.2 g of carbon disulfide and shake slowly for 5 hours;
[0086] Step 4: Place the above sponge in 250 mL of 1 M hydrochloric acid solution, desorb the copper ions, wash with water, and air-dry to obtain an adsorbent, and use the adsorbent to conduct an adsorption experiment. The adsorbent is numbered APS-7.
[0087] Example 8
[0088] Step 1: prepare 35 mL of a 4% branched polyethyleneimine solution, adjust the pH to 6.5 with nitric acid, slowly add the solution into 500 mL of a 0.8% sodium alginate solution while stirring to obtain a second mixed solution, pour the second mixture into a container and place it in a -10°C environment for rapid freezing for 5 hours to obtain a gel sponge carrier;
[0089] Step 2: Place the gel sponge carrier in 250 mL of the first mixed solution, which contains 0.5% genipin (w / w) and 1 g / L Cu 2+ , and then slowly shaken at room temperature for 5 hours to obtain a cross-linked sponge carrier;
[0090] Step 3: Place the cross-linked sponge carrier in 250 mL of alkaline solution containing 0.15 g of carbon disulfide and shake slowly for 5 hours;
[0091] Step 4: Place the above sponge in 250 mL of 1 M hydrochloric acid solution, desorb the copper ions, wash with water, and air-dry to obtain an adsorbent, and use the adsorbent to conduct an adsorption experiment. The adsorbent is numbered APS-8.
[0092] Example 9
[0093] Step 1: prepare 35 mL of a 4% branched polyethyleneimine solution, adjust the pH to 6.5 with nitric acid, slowly add the solution into 500 mL of a 0.8% sodium alginate solution while stirring to obtain a second mixed solution, pour the second mixture into a container and place it in a -10°C environment for rapid freezing for 5 hours to obtain a gel sponge carrier;
[0094] Step 2: Place the gel sponge carrier in 250 mL of the first mixed solution, which contains 0.5% genipin (w / w) and 1 g / L Cu 2+ , and then slowly shaken at room temperature for 5 hours to obtain a cross-linked sponge carrier;
[0095] Step 3: Place the cross-linked sponge carrier in 250 mL of alkaline solution containing 1.3 g of carbon disulfide and shake slowly for 5 hours;
[0096] Step 4: Place the above sponge in 250 mL of 1 M hydrochloric acid solution, desorb the copper ions, wash with water, and air-dry to obtain an adsorbent, and use the adsorbent to conduct an adsorption experiment. The adsorbent is numbered APS-9.
[0097] Example 10
[0098] Step 1: prepare 35 mL of a 4% branched polyethyleneimine solution, adjust the pH to 6.5 with nitric acid, slowly add the solution into 500 mL of a 0.8% sodium alginate solution while stirring to obtain a second mixed solution, pour the second mixture into a container and place it in a -10°C environment for rapid freezing for 5 hours to obtain a gel sponge carrier;
[0099] Step 2: Place the gel sponge carrier in 250 mL of the first mixed solution, which contains 0.2% genipin (w / w) and 1 g / L Cu 2+ , and then slowly shaken at room temperature for 5 hours to obtain a cross-linked sponge carrier;
[0100] Step 3: Place the cross-linked sponge carrier in 250 mL of alkaline solution containing 0.625 g of carbon disulfide and shake slowly for 5 hours;
[0101] Step 4: Place the above sponge in 250 mL of 1 M hydrochloric acid solution, desorb the copper ions, wash with water, and air-dry to obtain an adsorbent, and use the adsorbent to conduct an adsorption experiment. The adsorbent is numbered APS-10.
[0102] Embodiment 11
[0103] Step 1: prepare 35 mL of a 4% branched polyethyleneimine solution, adjust the pH to 6.5 with nitric acid, slowly add the solution into 500 mL of a 0.8% sodium alginate solution while stirring to obtain a second mixed solution, pour the second mixture into a container and place it in a -10°C environment for rapid freezing for 5 hours to obtain a gel sponge carrier;
[0104] Step 2: Place the gel sponge carrier in 250 mL of the first mixed solution, which contains 0.3% genipin (w / w) and 1 g / L Cu 2+ , and then slowly shaken at room temperature for 5 hours to obtain a cross-linked sponge carrier;
[0105] Step 3: Place the cross-linked sponge carrier in 250 mL of alkaline solution containing 0.625 g of carbon disulfide and shake slowly for 5 hours;
[0106] Step 4: Place the above sponge in 250 mL of 1 M hydrochloric acid solution, desorb the copper ions, wash with water, and air-dry to obtain an adsorbent, and use the adsorbent to conduct an adsorption experiment. The adsorbent is numbered APS-11.
[0107] Example 12
[0108] Step 1: prepare 35 mL of a 4% branched polyethyleneimine solution, adjust the pH to 6.5 with nitric acid, slowly add the solution into 500 mL of a 0.8% sodium alginate solution while stirring to obtain a second mixed solution, pour the second mixture into a container and place it in a -10°C environment for rapid freezing for 5 hours to obtain a gel sponge carrier;
[0109] Step 2: Place the gel sponge carrier in 250 mL of the first mixed solution, which contains 0.7% genipin (w / w) and 1 g / L Cu 2+ , and then slowly shaken at room temperature for 5 hours to obtain a cross-linked sponge carrier;
[0110] Step 3: Place the cross-linked sponge carrier in 250 mL of alkaline solution containing 0.625 g of carbon disulfide and shake slowly for 5 hours;
[0111] Step 4: Place the above sponge in 250 mL of 1 M hydrochloric acid solution, desorb the copper ions, wash with water, and air-dry to obtain an adsorbent, and use the adsorbent to conduct an adsorption experiment. The adsorbent is numbered APS-12.
[0112] Example 13
[0113] Step 1: prepare 35 mL of a 4% branched polyethyleneimine solution, adjust the pH to 6.5 with nitric acid, slowly add the solution into 500 mL of a 0.8% sodium alginate solution while stirring to obtain a second mixed solution, pour the second mixture into a container and place it in a -10°C environment for rapid freezing for 5 hours to obtain a gel sponge carrier;
[0114] Step 2: Place the gel sponge carrier in 250 mL of the first mixed solution, which contains 0.9% genipin (w / w) and 1 g / L Cu 2+ , and then slowly shaken at room temperature for 5 hours to obtain a cross-linked sponge carrier;
[0115] Step 3: Place the cross-linked sponge carrier in 250 mL of alkaline solution containing 0.625 g of carbon disulfide and shake slowly for 5 hours;
[0116] Step 4: Place the above sponge in 250 mL of 1 M hydrochloric acid solution, desorb the copper ions, wash with water, and air-dry to obtain an adsorbent, and use the adsorbent to conduct an adsorption experiment. The adsorbent is numbered APS-13.
[0117] Embodiment 14
[0118] Step 1: prepare 35 mL of a 4% branched polyethyleneimine solution, adjust the pH to 6.5 with nitric acid, slowly add the solution into 500 mL of a 0.8% sodium alginate solution while stirring to obtain a second mixed solution, pour the second mixture into a container and place it in a -10°C environment for rapid freezing for 5 hours to obtain a gel sponge carrier;
[0119] Step 2: Place the gel sponge carrier in 250 mL of the first mixed solution, which contains 0.4% glutaraldehyde (w / w) and 1 g / L Cu 2+ , and then slowly shaken at room temperature for 5 hours to obtain a cross-linked sponge carrier;
[0120] Step 3: Place the cross-linked sponge carrier in 250 mL of alkaline solution containing 0.625 g of carbon disulfide and shake slowly for 5 hours;
[0121] Step 4: Place the above sponge in 250 mL of 1 M hydrochloric acid solution, desorb the copper ions, wash with water, and air-dry to obtain an adsorbent, and use the adsorbent to conduct an adsorption experiment. The adsorbent is numbered APS-14.
[0122] The adsorbents obtained in Examples 1 to 14 and Comparative Example 1 were used to perform an adsorption experiment to adsorb the copper ions in the adsorption solution corresponding to Table 1, and then a desorption experiment was performed. In the adsorption experiment, 2.0000 g of sponge-like adsorbent was placed in 100 mL of Cu 2+ with Fe 3+ The solution (i.e. the raffinate after extraction of copper concentrate leaching solution, the composition is shown in Table 1) was shaken for 5 hours; Desorption experiment: the sponge-like adsorbent was taken out, washed and squeezed, and then placed in 100mL 1M hydrochloric acid solution, shaken for 1 hour, the sponge-like adsorbent was taken out, washed and squeezed, and then air-dried to measure its mass. The test results are shown in Table 2.
[0123] Table 2
[0124]
[0125] It can be seen from Table 2 that the adsorbent in Example 1 has a 2+ The selective adsorption effect is good, the αCu / Fe separation coefficient reaches 157.7, and the mass loss of APS-1 is only 0.02%. In practical applications, the number of times the adsorbent is replenished can be greatly reduced, thereby improving the adsorption efficiency.
[0126] In Example 2, the APS-2 adsorbent has a lower porosity than APS-1, which is more suitable for Cu 2+ The adsorption effect of APS-3 is relatively poor, and the adsorption amount is only 18.5 mg / g. 2+ The selectivity is not worse than that of Example 1, but due to the higher cross-linking pH, the cross-linking effect is worse than that of Example 1, and the mass loss reaches 0.29%.
[0127] In Example 4, the freezing temperature is controlled higher than that in Example 1, resulting in sponge shrinkage, low porosity, and poor adsorption effect compared to APS-1.
[0128] Comparative Example 1 did not undergo molecular imprinting treatment, and its 2+ Poor selectivity.
[0129] In Example 5, the adsorbent is effective for Cu 2+ The selective adsorption of was not significantly improved compared with Example 1, but instead caused a waste of Cu in the adsorbent preparation process.
[0130] According to the test data of Examples 6 to 9, it can be seen that if the amount of CS2 added is too low, the adsorption effect is poor, so the copper ion adsorption in Example 8 is low. If the amount of CS2 added is too high, too much secondary amine participates in the affinity addition reaction, resulting in the disintegration of the cross-linking between part of the sodium alginate and polyethyleneimine, and the stability of the adsorbent is reduced. Therefore, the adsorbent loss in Example 9 is large.
[0131] According to the test data of Examples 10 to 13, it can be seen that if the concentration of the cross-linking agent genipin is too low, the degree of cross-linking is low, and the stability of the adsorbent is poor, so the adsorbent loss in Example 10 is large. If the concentration of genipin is too high, too many primary amines participate in the cross-linking reaction, resulting in a decrease in the primary amines participating in the adsorption, a poor adsorption effect, and low selectivity, so the copper ion adsorption amount in Example 13 is low.
[0132] According to the test data of Example 14, it can be seen that if glutaraldehyde is used as a cross-linking agent, the adsorbent obtained has a stable adsorption effect on copper, a separation coefficient, and an adsorbent stability. It can be seen that in this application, using glutaraldehyde or genipin as an adsorbent can prepare an adsorbent with good performance.
[0133] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0134] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0135] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. Preparation of Cu adsorption 2+ The method of the adsorbent is characterized in that include: preparing a gel sponge carrier, wherein the gel sponge carrier has an amine group; The gel sponge carrier is placed in a first mixed solution and reacted for a predetermined time to obtain a cross-linked sponge carrier, wherein the first mixed solution contains a cross-linking agent and Cu 2+ ; placing the cross-linked sponge carrier in an alkaline solution containing carbon disulfide and shaking it for a predetermined time to obtain a pre-adsorbent; The pre-adsorbent is placed in an acid solution to react for a certain period of time, and then washed and dried to obtain the adsorbent. The method for preparing the gel sponge carrier comprises: Providing a polyethyleneimine solution and an alginate solution, wherein the pH value of the polyethyleneimine solution is 6.2-6.8; adding the polyethyleneimine solution to the alginate solution to obtain a second mixed solution; The second mixed solution is subjected to freezing treatment to obtain the gel sponge carrier, The freezing temperature is -50°C to -10°C; The cross-linking agent includes genipin, and the mass percentage of the genipin in the first mixed solution is 0.3% to 0.7%, and / or the cross-linking agent includes glutaraldehyde, and the mass percentage of the glutaraldehyde in the first mixed solution is 0.25% to 0.60%; In the first mixed solution, Cu 2+ The concentration is greater than 0 and less than or equal to 2g / L; The concentration of carbon disulfide in the alkali solution is 0.20 g / 250 mL to 1.20 g / 250 mL.
2. The method according to claim 1, characterized in that The polyethyleneimine in the polyethyleneimine solution is branched polyethyleneimine, which includes primary amine groups, secondary amine groups and tertiary amine groups.
3. The method according to claim 1, characterized in that The mass percentage of polyethyleneimine in the polyethyleneimine solution is 2% to 8%, and the concentration of alginate in the alginate solution is 0.5% to 1.2%.
4. The method according to claim 1, characterized in that: The concentration of hydrogen ions in the acid solution is greater than or equal to 1 mol / L.
5. A Cu adsorption 2+ The adsorbent is characterized in that The method is prepared by any one of claims 1 to 4.
Citation Information
Patent Citations
Preparation method and application of heavy metal ion absorbent
CN104907051A